2018
DOI: 10.2147/ijn.s185259
|View full text |Cite
|
Sign up to set email alerts
|

Co-exposure subacute toxicity of silica nanoparticles and lead acetate on cardiovascular system

Abstract: BackgroundThe harmful effects following the release of nanomaterials into environment are of great concern today.PurposeIn this study, subacute effect due to co-exposure to low-dose silica nanoparticles (SiNPs) and lead acetate (Pb) on cardiovascular system was detected in Sprague Dawley male rats.Materials and MethodsHistopathological and ultrastructural changes of heart, aortic arch and abdominal aorta were detected. Blood routine and blood biochemistry examinations were used to show the changes of blood com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 45 publications
0
21
2
Order By: Relevance
“…Wu et al [23] observed that co-exposure of nSiO 2 and benzo(a)pyrene causes synergistic toxicity to human bronchial epithelial (BEAS-2B) cells. Co-exposure of nSiO 2 and methylmercury (MeHg) or lead (Pb) induces synergistic cardiac toxicity [24,25]. The nSiO 2 and Pb co-exposure induces joint toxicity to human lung epithelial cells (A549) [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [23] observed that co-exposure of nSiO 2 and benzo(a)pyrene causes synergistic toxicity to human bronchial epithelial (BEAS-2B) cells. Co-exposure of nSiO 2 and methylmercury (MeHg) or lead (Pb) induces synergistic cardiac toxicity [24,25]. The nSiO 2 and Pb co-exposure induces joint toxicity to human lung epithelial cells (A549) [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…We attempted similar experiments with B[a]P, but could not detect any genotoxic potential of this substance in RAW 264.7 cells. The synergistic interaction of SiO 2 particles with co-contaminants has been reported in various studies, particularly with metals, such as cadmium, methylmercury, arsenic, and lead [13,14,[40][41][42][43][44], or with B[a]P [10][11][12]. Increased genotoxic potential has been highlighted for SiO 2 and B[a]P in epithelial cells [10,11,44].…”
Section: Discussionmentioning
confidence: 94%
“…Table 5 shows that the p(AAPBA-b-PTE) NPs did not greatly affect the blood biochemical indexes of mice compared with the normal group. Lin [49] et al observed the subacute effects of low-dose combined poisoning with silica NPs (SiNPs) and lead acetate (PB) on the cardiovascular system of SD rats through blood routine and blood biochemical analysis. It was also indirectly demonstrated that p(AAPBA-b-PTE)…”
Section: Toxicological Researchmentioning
confidence: 99%